Bone metabolism abnormalities in children with epilepsy at Red Cross War Memorial Children's Hospital, Cape Town, South Africa - Kija, Edward Nkingwa (Division of Urology, 2018)
Introduction: Epilepsy is the most common neurological condition worldwide. Literature on the antiepileptic medications and biochemical markers of bone metabolism has revealed inconsistent results. Most of these studies were undertaken in Europe and America where the burden and the associated comorbidities are different to the ones in Africa. Methods: A hospital based case control study was undertaken at Red Cross War Memorial Children's Hospital where children were recruited from a dedicated Epilepsy clinic and controls were obtained from a day surgical ward. Blood and urine samples were taken for the assessment of markers of bone metabolism. Results: Seventy-five cases and 75 controls were recruited. The median age for the children with epilepsy was 9 years with a range of 1 to 17 and controls 3 years with a range of 1 to 12. Vitamin D deficiency was present in 11(16.2%) of children with epilepsy compared to 6(8.8%) in the control group. Vitamin D insufficiency was present in 30(44.1%) in children with epilepsy compared to 27(39.7%) in the control group. Children with epilepsy on enzyme inducing AEDs had lower mean Vitamin D levels (24.67±11.4 vs 30.72±7.4, p=0.08), lower mean Vitamin D2 (0.25±0.07 vs 0.4±0.17,p=0.0018),lower mean Vitamin D3 (1.61±1.06 vs 2.58±0.86,p=0.004), lower mean serum phosphate levels (1.39±0.2 vs 1.76±0.7,p=0.000) and a higher mean parathyroid hormone levels (4.47±2.33 vs 2.7±0.97, p=0.03) compared to the control group. Children with Epilepsy on enzyme inhibitors had higher mean Vitamin D2 (0.44±0.37 vs 0.25±0.07,p=0.000004) and mean Vitamin D3 (2.26±0.86 vs 1.61±1.06,p=0.028) compared to children on enzyme inducers. Dietary intake and ancestry did not influence Vitamin D levels between the cases and controls. Conclusion and Recommendations: Vitamin D deficiency is common in children with epilepsy on AEDs. Children on enzyme inducing AEDs should be investigated for vitamin D deficiency and managed accordingly.